Assessing the impact of large‐scale water table modifications on riparian trees: a case study from Australia. Issue 4 (1st August 2014) - Pfautsch, Sebastian; Dodson, Wade; Madden, Sally; Adams, Mark A.
Abstract Mining below groundwater tables is increasing globally, yet little is known of how associated large‐scale modification of water tables impact functioning of surrounding ecosystems. We used measurements of foliage density (ρF) and sapwood‐related sap flow (QS) to assess effects of depth to groundwater on Eucalyptus victrix, a tree species that is common in riparian zones in central and northern parts of Australia. Foliage density (ρF) varied with season and among sites. Of itself, ρF provided a partial indicator of how trees responded to falling (more than 10 m) and rising (more than 9 m) water tables. Assessment of QS was highly informative. Across all sites, QS was least (90–130 l m−2 sapwood h−1) where groundwater was naturally deep (30 m) or had fallen substantially over the past 4 years (from 8 to 19 m). Fastest rates of QS (>245 l m−2 sapwood h−1) were recorded where groundwater had risen to a depth similar to a site where depth to groundwater remained stable at 6–7 m. Our analyses of daytime and night‐time QS emphasize that water use by E. victrix is highly plastic and opportunistic. We discuss how empirical analysis of QS, coupled with a sound understanding of local hydrogeology, can help assess responses in ecosystem function to large‐scale modification of groundwater levels – an important issue globally, as well as in Australia. Copyright © 2014 John Wiley & Sons, Ltd.